Porous NiTi alloy and preparation method thereof
Through metal injection molding combined with spherical pore-forming agent PMMA and double degreasing treatment, the problem of difficult control of porous NiTi alloy preparation is solved, and a high-performance porous NiTi alloy preparation is achieved, with small pore size, wide porosity and excellent mechanical properties. And low in impurities.
Patent Information
- Application Number
- CN202411422610.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The pore parameters in the preparation of porous NiTi alloys are difficult to control. The prior art has shortcomings in the preparation of high porosity and large pore size, and the pore structure and shape are not ideal, which affects performance.
Using metal injection molding combined with spherical pore forming agent PMMA, the pore forming agent is uniformly mixed with NiTi alloy raw material powder, and the binder with low melting point and high melting point components is added to perform double degreasing and thermal degreasing treatment to achieve The controllable pore parameters are obtained to obtain a uniformly distributed nearly spherical pore structure.
The porous NiTi alloy has a smaller pore size (up to 20μm at minimum), a wider porosity range (20~80%), and a uniform pore size distribution, which improves mechanical properties, and reduces carbon and oxygen content, obtains low impurities and high Performance porous NiTi alloy.
Smart Images

Figure CN119194150A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy manufacturing, and in particular relates to a porous NiTi alloy and a preparation method thereof. Background Art
[0002] Porous NiTi alloy has good mechanical properties, excellent corrosion resistance and biocompatibility, high elastic yield stress, compressibility and porous structure can also cooperate with fibrous tissue and bone tissue, and has a high market prospect in the medical field. Therefore, in the preparation of porous NiTi alloy, in addition to obtaining high performance under similar porosity, it is necessary to achieve controllable preparation of pore parameters, including porosity, pore size, pore shape, pore distribution, etc.
[0003] Common powder metallurgy preparation technologies for porous NiTi alloys include powder sintering (PS), microwave sintering (MS), self-propagating high temperature synthesis (SHS), hot isostatic pressing (HIP), and spark plasma sintering (SPS).
[0004] The traditional powder sintering method reduces the pressing pressure of powder compaction to perform loose sintering. The sintering pores of porous NiTi alloy mainly come from the powder stacking gap caused by the reduction of pressing pressure. The traditional powder sintering method has the advantages of simple operation, easy control and high yield, but it only relies on the pores formed by the powder stacking gap, which is insufficient in the preparation of porous NiTi alloy with higher porosity and larger pore size.
[0005] Microwave sintering is a preparation method that couples materials with microwaves, absorbs electromagnetic energy and converts it into heat energy to achieve alloying. Microwave sintering has the advantages of low energy consumption, fast heating, short sintering time, and enhanced element diffusion. However, microwave sintering has obvious shortcomings in the preparation of porous NiTi alloys with higher porosity.
[0006] Self-propagating high-temperature sintering has the advantages of fast speed, simple operation and low cost, and can prepare porous NiTi alloys with large porosity. Researchers have studied the effects of different preparation parameters such as billet density, heating rate, preheating temperature, powder chemical composition and ignition method on the properties of the prepared NiTi porous alloy. The pores prepared by self-propagating high-temperature sintering will be distributed in lamellar shapes vertically along the ignition direction, and the pore shape is difficult to effectively control, and the porous material will have anisotropy of performance, which seriously affects the performance of porous NiTi alloys.
[0007] Hot isostatic pressing is a process of applying high temperature and high pressure in a special container at the same time. Some gas is trapped in the gaps between metal powders during hot isostatic pressing. The gas expands and foams during the subsequent sintering process to form pores, thus obtaining porous NiTi alloy. However, the pore structure of porous NiTi alloy produced by this method is not ideal, and the porosity and pore size are difficult to control.
[0008] Electrospark plasma sintering is a pressure-assisted pulse current sintering process that uses instantaneous spark discharges in the powder gap. It is a very effective, convenient and rapid preparation method for metals, ceramics, composites and porous materials, with the advantages of rapid forming and finer alloy grains. Compared with traditional sintering, the rate of forming sintering necks in electrospark plasma sintering is faster, and the electric field diffusion effect generated during the preparation process can purify the particle surface to improve the sintering quality. However, electrospark plasma sintering does not have enough sintering accuracy for the final workpiece and requires post-sintering processing, which lacks competitiveness in the preparation of small precision parts.
[0009] Porous NiTi alloys pursue controllable preparation of pore parameters, and porous alloys with high sphericity have better performance. The above-mentioned traditional powder metallurgy technologies are all lacking in controllable preparation of pore parameters. In order to meet the market's extensive demand for porous NiTi alloys, in recent years, the method of preparing porous NiTi alloys by additive manufacturing or other preparation processes combined with pore-forming agent method has become the mainstream in the field. Additive manufacturing is a type of preparation method with extremely high freedom in pore parameter design, especially for complex pores with diameters of 100-1000 μm. However, due to the limitations of light source diameter and equipment accuracy, the quality of the pore wall decreases as the pore diameter decreases. There are few reports on the preparation of porous NiTi alloys with pores <100 μm in diameter by additive manufacturing.
[0010] Metal injection molding technology combined with pore-forming agent method (MIM-PSH) is a type of method suitable for preparing porous materials and gradient porous materials. MIM has the advantage of near-net forming and can realize large-scale production of small and complex parts. In addition, the volume fraction of the binder used in the MIM process is large (40-60 vol.%), which helps to evenly mix the powder and the placeholder particles. The design of combining the pore-forming agent removal step with the MIM binder degreasing can simplify the preparation process combined with the pore-forming agent method to a certain extent. However, there have been few reports on the preparation of porous NiTi alloys using the MIM-PSH method. In the existing MIM-PSH method, the simultaneous removal of pore-forming agents and binders has always been a difficult problem to overcome in the field, and it will also significantly affect the performance of the prepared porous NiTi alloy. Therefore, there is still a lack of a pore parameter control method for the preparation of porous NiTi alloys. Summary of the invention
[0011] The technical problem to be solved by the present invention is that the pore parameters of porous NiTi alloy preparation are difficult to control, and the deficiencies and defects mentioned in the above background technology are overcome to provide a porous NiTi alloy and a preparation method thereof.
[0012] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a porous NiTi alloy comprises the following steps: (1) Screening a pore-forming agent and uniformly mixing the pore-forming agent with NiTi alloy raw material powder; the pore-forming agent is a high molecular weight polymethyl methacrylate; (2) adding a binder, mixing, granulating, and injection molding to obtain a green body; the binder comprises three components: a low melting point component, a high melting point component, and a surfactant; wherein the low melting point component comprises at least one of paraffin wax, polyethylene glycol, montan wax, polystyrene, or beeswax, the high melting point component comprises at least one of high density polyethylene, polypropylene, or ethylene-vinyl acetate copolymer, and the surfactant comprises stearic acid; (3) After the green body is subjected to solvent degreasing treatment, thermal degreasing is performed, wherein the thermal degreasing heating rate is 1-3°C / min, the temperature is 500-600°C, the time is 1-2h, the thermal degreasing atmosphere is an inert gas atmosphere, and the air flow pressure is 1000-2000Pa; (4) The degreased green body obtained in step (3) is vacuum sintered at 1200-1250° C. to obtain a porous NiTi alloy.
[0013] The preparation method of the present invention screens and controls the size and shape of the pore-forming agent PMMA, and evenly mixes it with NiTi pre-alloy powder and a binder to achieve controllable preparation of porous alloy pore parameters, thereby obtaining a uniformly distributed, nearly spherical porous NiTi alloy with different pore diameters and porosities.
[0014] NiTi alloy powder usually has extremely high activity. The key difficulty in the MIM manufacturing process is to control the low carbon content and oxygen content. In many previous porous material preparation methods, pore formers such as NaCl and NH4CO3 need to be removed in a variety of media (such as water, ethanol, etc.) or during heating, which cannot be integrated with the MIM process, increasing the risk of oxidation. In addition, due to the irregular shape of the pore former, it is difficult to obtain spherical pores. PMMA is usually spherical, cheap and easy to obtain, and can obtain nearly spherical pores, which is beneficial to improve mechanical properties.
[0015] In the existing MIM technology, there are only a few reports on the use of PMMA as a pore former, which is mostly used in materials such as stainless steel and alloy steel that have low requirements for carbon and oxygen impurity content, and rarely appears in titanium alloys and nickel-titanium alloys. In the present invention, PMMA is used as a pore former, and a binder containing a low melting point component (such as paraffin) with a low softening temperature is selected, so that the binder is in a fluid state during the injection process and the pore former remains in a solid state, and a uniform pore distribution is obtained after degreasing and sintering; at the same time, the combination of this binder and pore former enables them to be removed simultaneously in the solvent degreasing-thermal degreasing step, and no additional steps are required in the MIM preparation process, and finally a nearly spherical porous NiTi alloy with a low carbon content and oxygen content is prepared, and extremely high mechanical properties are obtained.
[0016] The present invention adopts a double degreasing scheme of solvent degreasing and thermal degreasing. The solvent degreasing is relatively slow and can form channels without generating bubbles and cracks, so as to facilitate the rapid decomposition and removal of the binder in the subsequent thermal degreasing stage.
[0017] Preferably, the binder comprises paraffin wax, high-density polyethylene and stearic acid, and the mass ratio of the paraffin wax, high-density polyethylene and stearic acid is 50-70%: 29-40%: 1-10%, which is 100% in total.
[0018] Preferably, the thermal degreasing heating rate is 1-3°C / min, the temperature is 500-600°C, the time is 1-2h, the thermal degreasing atmosphere is an inert gas atmosphere, and the airflow pressure is 1000-2000Pa.
[0019] Taking advantage of the similar dissolution properties and thermal decomposition temperatures of PMMA and binders in organic solvents, the pore former and binder are removed simultaneously in the MIM degreasing process to reduce additional steps. When the NiTi alloy is above 600°C, the TiO2 protective layer on the surface begins to dissolve, and a lower degreasing temperature can reduce powder oxidation; only above 500°C can the binder and PMMA be completely removed, so thermal degreasing is performed in the temperature range of 500-600°C to ensure that the binder and pore former are completely removed while reducing NiTi powder oxidation. At the same time, using an inert atmosphere to protect the product during the thermal degreasing process can further reduce the risk of powder oxidation.
[0020] Preferably, the pore-forming agent is high molecular weight polymethyl methacrylate, and the binder includes paraffin wax, high-density polyethylene (HDPE) and stearic acid, and the mass ratio of the paraffin wax, high-density polyethylene and stearic acid is 50-70%: 29-40%: 1-10%, which is 100% in total.
[0021] The preferred pore former and binder of the present invention can make the workpiece have good shape retention at room temperature and good fluidity at injection temperature, and the pore former maintains a certain hardness during the injection process, maintains the pore morphology, and synergistically obtains a nearly spherical uniform porous structure; at the same time, the above-mentioned pore former and binder have similar decomposition temperatures, and can be synchronously and completely removed through the thermal degreasing step.
[0022] Preferably, the mass ratio of the pore former to the NiTi alloy raw material powder is 20-60%, and the mass ratio of the binder to the sum of the mass of the NiTi alloy raw material powder and the pore former is 7-9%.
[0023] Preferably, the screening particle size of the screening pore-forming agent is 20-1000 μm, the mixing adopts mechanical powder mixing, the powder mixing speed is less than 60 r / min, and the mixing time is not less than 24 hours. The pore structure obtained by the present invention is highly correlated with the size of the pore-forming agent. By strictly controlling the parameters of the pore-forming agent, the controllability of the porous structure can be improved, and the customized preparation of porous NiTi alloy can be achieved.
[0024] Preferably, the banburying temperature is not higher than 200° C., the banburying is carried out in an Ar atmosphere, and the banburying time is 2 to 4 hours.
[0025] Preferably, the mold temperature of the compression injection molding is 50° C., the injection temperature is 130-170° C., the injection pressure is 70-120 MPa, and the injection rate is 40-80 g / s.
[0026] Preferably, the solvent degreasing adopts dichloromethane solution at 30-40° C. for immersion degreasing, and the immersion time is not less than 10 hours.
[0027] Preferably, the vacuum degree of the vacuum sintering is not less than 10 -4 Pa, sintering time is not less than 5h.
[0028] Under the same technical concept, the present invention also provides a porous NiTi alloy, which is prepared by the above-mentioned preparation method. The porous NiTi alloy has a nearly spherical morphology, a porosity of 21~53%, a compressive yield strength of 350~1317MPa, a recovery rate under 8% compressive prestrain higher than 70%, a carbon content lower than 0.05wt.%, and an oxygen content lower than 0.30wt.%.
[0029] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the present invention proposes to use metal injection molding combined with spherical pore former PMMA, and to achieve controllable preparation of porous alloy pore parameters by regulating PMMA powder parameters and addition ratio, thereby obtaining a porous NiTi alloy with uniformly distributed near-spherical shape, different pore sizes and porosities. The porous NiTi alloy can be prepared with a smaller controllable pore size (down to 20 μm), a wider range of selectable porosity (20-80% porosity), and a uniform pore size distribution, which is conducive to obtaining a porous NiTi alloy with controllable pore structure and high mechanical properties; (2) The porous NiTi alloy prepared by the preparation method of the present invention has near-spherical pores with higher performance through adjusting the pore parameters. In addition, through a suitable two-step degreasing and vacuum sintering process, the pore former and binder are completely removed and oxidation problems are avoided. The carbon content in the final alloy product is less than 0.05wt.%, and the final oxygen content is less than 0.30wt.%. The preparation of low-impurity porous NiTi alloy is achieved, and the preparation energy consumption is low. The scheme is easy to operate and implement, and has good industrial prospects and market value. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 is a flow chart of preparing a porous NiTi alloy according to an embodiment of the present invention; Figure 2 is a SEM morphology image of the NiTi pre-alloyed powder in Example 1 of the present invention; Figure 3 is a SEM morphology image of the pore-forming agent PMMA in Example 1 of the present invention; Figure 4 The cross-sectional SEM morphology of the samples added with different volume ratios of pore formers in Examples 1-3 of the present invention after degreasing and sintering; Figure 5 The three-dimensional CT reconstruction images of the porous structures of Examples 1-3 of the present invention are as follows: (a) is Example 1, (b) is Example 2, and (c) is Example 3; Figure 6 The pore size distribution of Examples 1-3 of the present invention according to image statistics: (a) is Example 1, (b) is Example 2, and (c) is Example 3; Figure 7 It is the compressive engineering stress-strain curve of the samples added with pore-forming agents in different volume ratios after degreasing and sintering in Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0033] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0035] Example 1 This embodiment provides a method for preparing a porous NiTi alloy. The preparation process is as follows: Figure 1 As shown, the specific steps are as follows: (1) High-purity pre-alloyed NiTi powder was mixed with 20 vol.% PMMA through a 200-mesh sieve for 24 h at a mixing speed of 60 r / min to obtain a uniformly mixed NiTi+PMMA powder. The SEM morphology of the NiTi pre-alloyed powder is shown in Figure 2. Figure 2 As shown, the SEM morphology of the pore-forming agent PMMA is as follows Figure 3 As shown; (2) Add 8.5 wt.% of a multi-component binder to the uniformly mixed NiTi+PMMA powder, wherein the mass composition of the multi-component binder is 60% paraffin + 35% high-density polyethylene + 5% stearic acid; and knead the powder in an internal mixer at 150 °C with argon for 2 h, and then prepare the feed into granules; and prepare the green body by injection molding under the injection molding process parameters of injection temperature of 140 °C, injection pressure of 80 MPa, injection rate of 50 g / s, and mold temperature of 50 °C; (3) The green body was immersed in a 32 °C dichloromethane solution for 20 h for solvent degreasing. After degreasing, the sample was thermally degreased at 570 °C for 1 h in an argon flow sintering furnace. The cross-sectional SEM morphology of the pore-forming agent sample after degreasing and sintering is shown in Figure 2. Figure 4 As shown; (4) Place the thermally degreased sample at 5×10 -4 The porous NiTi alloy was obtained by vacuum sintering at 1240 °C for 6 h in a vacuum sintering furnace with a vacuum degree of Pa.
[0036] The porous NiTi alloy prepared in this example was subjected to a compressive stress-strain curve performance test. The test method was based on the standard ASTM E9-09. The test results are shown in FIG. Figure 7The compression recovery rate calculation formula is as follows: ; Where R is the compression recovery rate, h 0 is the original sample height, h 1 is the height of the sample after heating, ɛ ɑ is the applied strain.
[0037] Example 2 This embodiment provides a method for preparing a porous NiTi alloy. The preparation process is as follows: Figure 1 As shown, the specific steps are as follows: (1) High-purity pre-alloyed NiTi powder was mixed with 40 vol.% PMMA through a 200-mesh sieve for 24 h at a mixing speed of 60 r / min to obtain a uniformly mixed NiTi+PMMA powder. The SEM morphology of the NiTi pre-alloyed powder is shown in Figure 2. Figure 2 As shown, the SEM morphology of the pore-forming agent PMMA is as follows Figure 3 As shown; (2) Add 8.5 wt.% of a multi-component binder to the uniformly mixed NiTi+PMMA powder, wherein the mass composition of the multi-component binder is 60% paraffin + 35% high-density polyethylene + 5% stearic acid; and knead the powder in an internal mixer at 150 °C with argon for 2 h, and then prepare the feed into granules; and prepare the green body by injection molding under the injection molding process parameters of injection temperature of 140 °C, injection pressure of 80 MPa, injection rate of 50 g / s, and mold temperature of 50 °C; (3) The green body was immersed in a 32 °C dichloromethane solution for 20 h for solvent degreasing. After degreasing, the sample was thermally degreased at 570 °C for 1 h in an argon flow sintering furnace. The cross-sectional SEM morphology of the pore-forming agent sample after degreasing and sintering is shown in Figure 2. Figure 4 As shown; (4) Place the thermally degreased sample at 5×10 -4 The porous NiTi alloy was obtained by vacuum sintering at 1230 °C for 6 h in a vacuum sintering furnace with a vacuum degree of Pa.
[0038] The porous NiTi alloy prepared in this example was subjected to a compressive stress-strain curve performance test. The test results are as follows: Figure 7 shown.
[0039] Example 3 This embodiment provides a method for preparing a porous NiTi alloy. The preparation process is as follows: Figure 1 As shown, the specific steps are as follows: (1) High-purity pre-alloyed NiTi powder was mixed with 60 vol.% PMMA through a 200-mesh sieve for 24 h at a mixing speed of 60 r / min to obtain a uniformly mixed NiTi+PMMA powder. The SEM morphology of the NiTi pre-alloyed powder is shown in Figure 2. Figure 2 As shown, the SEM morphology of the pore-forming agent PMMA is as follows Figure 3 As shown; (2) Add 8.5 wt.% of a multi-component binder to the uniformly mixed NiTi+PMMA powder, wherein the mass composition of the multi-component binder is 60% paraffin + 35% high-density polyethylene + 5% stearic acid; and knead the powder in an internal mixer at 150 °C with argon for 2 h, and then prepare the feed into granules; and prepare the green body by injection molding under the injection molding process parameters of injection temperature of 140 °C, injection pressure of 80 MPa, injection rate of 50 g / s, and mold temperature of 50 °C; (3) The green body was immersed in a 32 °C dichloromethane solution for 20 h for solvent degreasing. After degreasing, the sample was thermally degreased at 570 °C for 1 h in an argon flow sintering furnace. The cross-sectional SEM morphology of the pore-forming agent sample after degreasing and sintering is shown in Figure 2. Figure 4 As shown; (4) Place the thermally degreased sample at 5×10 -4 The porous NiTi alloy was obtained by vacuum sintering at 1250 °C for 6 h in a vacuum sintering furnace with a vacuum degree of Pa.
[0040] Figure 5 These are three-dimensional CT reconstruction images of the porous structures of Examples 1-3 of the present invention: (a) is Example 1, (b) is Example 2, and (c) is Example 3.
[0041] Figure 6 Embodiments 1-3 of the present invention are based on Figure 5 The pore size distribution of the images: (a) is Example 1, (b) is Example 2, and (c) is Example 3.
[0042] The porous NiTi alloy prepared in this example was subjected to a compressive stress-strain curve performance test. The test results are as follows: Figure 7 shown.
[0043] The performance of the porous NiTi alloys of Examples 1-3 was tested, wherein the compressive yield strength was tested according to ASTM E9-09. The test results are shown in Table 1 below.
[0044] Comparative Example 1 This comparative example provides a method for preparing a porous NiTi alloy, and the specific steps are as follows: (1) High-purity pre-alloyed NiTi powder and 40 vol.% NaCl particles sieved through a 100-mesh sieve were mixed for 24 h at a mixing speed of 60 r / min to obtain a uniformly mixed NiTi+NaCl powder; (2) Add 8.5 wt.% of a multi-component binder to the uniformly mixed NiTi+NaCl powder, wherein the mass composition of the multi-component binder is 60% paraffin + 35% high-density polyethylene + 5% stearic acid; and knead the powder in an internal mixer at 150 °C with argon for 2 h, and then prepare the granular feed; and inject the green body under the injection molding process parameters of injection temperature of 140 °C, injection pressure of 80 MPa, injection rate of 50 g / s, and mold temperature of 50 °C; (3) The green body was immersed in a 32 °C dichloromethane solution for 20 h for solvent debinding; then immersed in 40 °C water for 24 h to remove NaCl; and then the sample was thermally debinded at 570 °C for 1 h in an argon flow sintering furnace; (4) Place the thermally degreased sample at 5×10 -4 The porous NiTi alloy was obtained by vacuum sintering at 1240 °C for 6 h in a vacuum sintering furnace with a vacuum degree of Pa.
[0045] The porous NiTi alloy finally obtained has irregular pore morphology, a porosity of about 36%, an average pore size of 125 μm, a carbon content of 0.06 wt.%, and an oxygen content of 0.45 wt.%. Its high carbon and oxygen content will lead to reduced material performance.
[0046] Comparative Example 2 This comparative example provides a method for preparing a porous NiTi alloy, and the specific steps are as follows: (1) High-purity pre-alloyed NiTi powder and 40 vol.% PMMA passed through a 200-mesh sieve were mixed for 24 h at a mixing speed of 60 r / min to obtain a uniformly mixed NiTi+PMMA powder; (2) Add 8.5 wt.% of a multi-component binder to the uniformly mixed NiTi+PMMA powder, wherein the mass composition of the multi-component binder is 60% polyoxymethylene + 35% polypropylene + 5% stearic acid; and knead the powder in an internal mixer at 170 °C with argon for 2 h, and then prepare the feed into granules; and prepare the green body by injection molding under the injection molding process parameters of injection temperature of 140 °C, injection pressure of 80 MPa, injection rate of 50 g / s, and mold temperature of 50 °C; (3) The green body was immersed in 80 °C nitric acid solution for 5 h for catalytic debinding; then immersed in 40 °C dichloromethane for 10 h to remove PMMA; and then the sample was thermally debound at 570 °C for 1 h in an argon flow sintering furnace; (4) Place the thermally degreased sample at 5×10 -4 The porous NiTi alloy was obtained by vacuum sintering at 1240 °C for 6 h in a vacuum sintering furnace with a vacuum degree of Pa.
[0047] The pores of the porous NiTi alloy obtained in the end are nearly spherical, with a porosity of about 34%, an average pore size of 45 μm, a carbon content of 0.07 wt.%, and an oxygen content of 0.35 wt.%. Its high carbon and oxygen content will lead to reduced material performance; at the same time, the use of plastic-based binders represented by polyoxymethylene, on the one hand, requires three degreasing steps, while reducing injection fluidity and increasing the difficulty of filling molds for precision and complex parts.
[0048] Table 1: Performance test results of porous NiTi alloys of Examples 1-3
Claims
1. A method for preparing a porous NiTi alloy, characterized in that: The following steps are involved: (1) Screening a pore-forming agent and uniformly mixing the pore-forming agent with NiTi alloy raw material powder; the pore-forming agent is a high molecular weight polymethyl methacrylate; (2) adding a binder, mixing, granulating, and injection molding to obtain a green body; the binder comprises three components: a low melting point component, a high melting point component, and a surfactant; wherein the low melting point component comprises at least one of paraffin wax, polyethylene glycol, montan wax, polystyrene, or beeswax, the high melting point component comprises at least one of high density polyethylene, polypropylene, or ethylene-vinyl acetate copolymer, and the surfactant comprises stearic acid; (3) After the green body is subjected to solvent degreasing treatment, thermal degreasing is performed; (4) The degreased green body obtained after step (3) is vacuum sintered at 1200-1250° C. to obtain a porous NiTi alloy.
2. The preparation method according to claim 1, characterized in that The binder comprises paraffin wax, high-density polyethylene and stearic acid, and the mass ratio of the paraffin wax, high-density polyethylene and stearic acid is 50-70%: 29-40%: 1-10%, which is 100% in total.
3. The preparation method according to claim 1, characterized in that: The thermal degreasing heating rate is 1-3°C / min, the temperature is 500-600°C, the time is 1-2h, the thermal degreasing atmosphere is an inert gas atmosphere, and the air flow pressure is 1000-2000Pa.
4. The preparation method according to claim 1 or 2, characterized in that: The volume ratio of the pore former to the NiTi alloy raw material powder is 20-60%, and the mass ratio of the binder to the sum of the mass of the NiTi alloy raw material powder and the pore former is 7-9%.
5. The preparation method according to claim 1 or 2, characterized in that: The screening particle size of the screening pore-forming agent is 20-1000 μm, and the mixing is performed by mechanical powder mixing, the powder mixing speed is less than 60 r / min, and the mixing time is not less than 24 h.
6. The preparation method according to claim 1 or 2, characterized in that: The temperature of the banburying is not higher than 200° C., the banburying is carried out in an Ar gas atmosphere, and the banburying time is 2 to 4 hours.
7. The preparation method according to claim 1 or 2, characterized in that: The injection temperature of the compression injection molding is 130-170° C., the injection pressure is 70-120 MPa, and the injection rate is 40-80 g / s.
8. The preparation method according to claim 1 or 2, characterized in that: The solvent degreasing adopts dichloromethane solution at 30-40° C. for immersion degreasing, and the immersion time is not less than 10 hours.
9. The preparation method according to claim 1 or 2, characterized in that: The vacuum degree of the vacuum sintering is not less than 10 - 4 Pa, sintering time is not less than 5h.
10. A porous NiTi alloy, characterized in that: The porous NiTi alloy is prepared by the preparation method described in any one of claims 1 to 9, and the porous NiTi alloy has a nearly spherical morphology, a porosity of 21-53%, a compressive yield strength of 350-1317 MPa, a recovery rate under 8% compressive prestrain higher than 70%, a carbon content lower than 0.05wt.%, and an oxygen content lower than 0.30wt.%.
Citation Information
Patent Citations
Injection molding method of titanium alloy part
CN110935878A
Foamed metal powder injection molding feed and preparation method thereof as well as foamed metal special-shaped part
CN112846169A
